Can laterality judgment performance discriminate between people with chronic pain and healthy individuals?: a systematic review and meta-analysis - Ravat, Sadiya (My University, 2017)
Background Chronic pain is a health problem that occurs across cultures and across the globe. Treatment of chronic pain is challenging and there is often failure of recovery, with the need to look at different approaches to understanding chronic pain. It was recently found that people with chronic pain have both central and peripheral features. Therefore, there is a need to look at central mechanisms that may be contributing to the chronicity of pain. People with chronic pain disorders experience a disturbance in body schema. Laterality judgment performance is dependent on body schema and can therefore determine the central mechanisms affected in chronic pain patients. The aim of this systematic review is to determine whether there is a difference in laterality judgment between people with chronic pain and healthy individuals. Method A comprehensive search was done of the following databases: MEDLINE (Pubmed), CINAHL Plus, Cochrane Controlled Trials Registered, Physiotherapy Evidence Database (PEDro), Science Direct, SCOPUS, Clinical Key and Google Scholar. Combinations of the following keywords were used: ―laterality‖ ―body schema‖ ―motor imagery‖ and ―pain‖. The reference lists of all identified full text articles were searched for additional studies. Articles from inception up until December 2016 were considered for inclusion in this review. Outcome measures considered were reaction time (length of time taken to choose whether a pictured limb is right or left) and accuracy (correct number of responses). A total of 15 studies were included in this review. Methodological quality was assessed by two independent reviewers using the Joanna Briggs Institute Critical Appraisal Checklist for Analytical Cross Sectional Studies. Results from all the studies investigating similar conditions and using similar methodologies were analysed and pooled into statistical meta-analysis using Meta-Easy. The weighted mean differences (for continuous data) and their 95% confidence intervals were calculated for the outcome measures, namely reaction time and accuracy. The random-effects model was used, due to the variation and small sample sizes in studies. Heterogeneity was assessed by the p-value and I2 value. Thereafter, studies were divided into sub-groups (according to condition/similar laterality tasks) and further iii analysed. Statistical measures used in both meta-analyses included the probability value, mean effect size, variance effect size and maximum likelihood. Where statistical pooling was not possible the findings are presented in a narrative form. Results Forest plots of reaction time of five studies regardless of condition in terms of reaction time showed a positive relationship between decreased reaction time and chronic pain. Accuracy of five studies regardless of condition did not show a clear direction of effect. Due to the high heterogeneity, interpretation of this meta-analysis should be done with caution. The sub-group analysis for accuracy in lower limb conditions versus healthy individuals showed a medium statistically significant effect size (0.59) with a significant 95% CI (0.11 to 1.07). Results for low back pain and cervical pain could not be pooled into a meta-analysis, as there were different methods of reporting the results in the studies. However, results from individual studies showed that laterality judgment impairments are present in the low back pain, complex regional pain syndrome 1 and the upper limb pain population. It was not been shown to be impaired in whiplash associated disorders. There is no consensus in the literature whether laterality is affected in chronic cervical pain. Conclusion Laterality judgment was shown to be impaired in CPRS 1, upper limb pain, carpal tunnel syndrome, and osteoarthritis of the knee and leg pain. Due to the lack of studies, low quality of evidence and differences in results between studies there are inconsistencies with regard to back pain and therefore no conclusions can be drawn from the literature. It was not been shown to be impaired in whiplash associated disorders and there is conflicting evidence in cervical pain. It is evident that the impairment of laterality judgment cannot be assumed amongst all chronic pain conditions. This systematic review can be used as a foundation for future research. Research studies can be designed to remediate laterality recognition in affected conditions and assess the effect hereof on levels of pain and functional abilities. This could solve the missing link in understanding chronic pain syndromes and its rehabilitation. Clinicians can also gain insight on incorporating techniques (e.g. graded motor imagery) to re-train the brain‘s neural plasticity, and to in turn decrease chronic pain.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of MSc Physiotherapy Johannesburg, 2017
Keywords: Chronic Pain